PENGARUH KARAKTERISTIK INDIVIDU DAN KARAKTERISTIK PEKERJAAN TERHADAP KEPUASAN KERJA DENGAN MEDIASI KOMITMEN ORGANISASIONAL - TM, Budiyanto; Abdul Rozak, Hasan (Students Journal of Economic and Management, 2012)
This study aimed to analyze the influence of individual characteristic and job characteristic to job satisfaction with the mediation of organizational commitment. The samples use 104 employees (civil servants) at the Secretariat of Batang Regency, the sampling techhique using purposive sampling method with criteria are minimal education is senior high school and have worked for at last 5 (five) years. The data was analysed by using multple regression method. The result of this research the proved that the individual characteristic, job characteristic and organizational commitment has 61 % contributed in explaining to the job satisfaction, while the 39 % other variables. The result of regression analysis proved that the individual characteristic and job characteristic have a positive impact on organizational commitment. Individual characteristic, job characteristic and organizational commitment have a positive impact on job satisfaction. Keywords : Individual characteristic, job characteristic, organizational commitment and job satisfaction